2019
DOI: 10.1101/555094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunohistochemical and ultrastructural analysis of the maturing larval zebrafish enteric nervous system reveals the formation of a neuropil pattern

Abstract: The gastrointestinal tract is constructed with an intrinsic series of interconnected ganglia that span its entire length, called the enteric nervous system (ENS). The ENS exerts critical local reflex control over many essential gut functions; including peristalsis, water balance, hormone secretions and intestinal barrier homeostasis. ENS ganglia exist as a collection of neurons and glia that are arranged in a series of plexuses throughout the gut: the myenteric plexus and submucosal plexus. While it is known t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Immunostaining signal for GFAP has previously reported in the ENS (Baker et al, 2019;Kelsh and Eisen, 2000), however in our experiments the expression is not apparently within the NC-derived lineages. Consistent with the immunostaining, expression of the Tg(gfap:GFP) transgene (Bernardos and Raymond, 2006) was also undetectable in the gut of 7dpf larvae (Fig.…”
Section: Expression Of Canonical Glia Markers Is Undetectable In the contrasting
confidence: 50%
See 2 more Smart Citations
“…Immunostaining signal for GFAP has previously reported in the ENS (Baker et al, 2019;Kelsh and Eisen, 2000), however in our experiments the expression is not apparently within the NC-derived lineages. Consistent with the immunostaining, expression of the Tg(gfap:GFP) transgene (Bernardos and Raymond, 2006) was also undetectable in the gut of 7dpf larvae (Fig.…”
Section: Expression Of Canonical Glia Markers Is Undetectable In the contrasting
confidence: 50%
“…Immunostaining signal detected with two antibodies specific for zebrafish GFAP ( Baker et al, 2019 ; Trevarrow et al, 1990 ) was likely to represent cross-reactivity with non-neuroectodermal gut tissues, as it persisted in ret mutant larvae, which lack enteric neuroglia networks ( Figure 1—figure supplement 1G–J ; Heanue et al, 2016a ). Immunostaining signal for GFAP has previously been reported in the ENS ( Baker et al, 2019 ; Kelsh and Eisen, 2000 ), however in our experiments the expression is not apparently within the NC-derived lineages. Consistent with the immunostaining, expression of the Tg(gfap:GFP) transgene ( Bernardos and Raymond, 2006 ) was also undetectable in the gut of 7 dpf larvae ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three papers reported contradicting findings regarding expression of canonical glial genes such as gfap, the traditional marker for enteric glia in human and mouse. Baker et al showed Gfap+ enteric glia in the outer layer of the intestine of 7 and 18 dpf fish, encapsulated by a layer of enteric neurons (10). Transmission electron microscopy showed the presence of granular vesicles and filiform processes wrapping the muscularis and caveolae, which are typical characteristic of glia (10).…”
Section: Introductionmentioning
confidence: 99%
“…showed Gfap+ enteric glia in the outer layer of the intestine of 7 and 18 dpf fish, encapsulated by a layer of enteric neurons (10). Transmission electron microscopy showed the presence of granular vesicles and filiform processes wrapping the muscularis and caveolae, which are typical characteristic of glia (10). McCallum et al .…”
Section: Introductionmentioning
confidence: 99%